2007
DOI: 10.1523/jneurosci.1170-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

EphA4 Signaling Regulates Phospholipase Cγ1 Activation, Cofilin Membrane Association, and Dendritic Spine Morphology

Abstract: Specialized postsynaptic structures known as dendritic spines are the primary sites of glutamatergic innervation at synapses of the CNS. Previous studies have shown that spines rapidly remodel their actin cytoskeleton to modify their shape and this has been associated with changes in synaptic physiology. However, the receptors and signaling intermediates that restructure the actin network in spines are only beginning to be identified. We reported previously that the EphA4 receptor tyrosine kinase regulates spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 79 publications
3
81
0
Order By: Relevance
“…S3o-r). In addition, we found that growth cone collapse coincides with phosphorylation of three potential downstream signalling proteins of EphA4: the guanine nucleotide exchange factor ephexin-1 30 , the actin-depolymerizing and -severing factor cofilin-1 31 and the ATP-dependent motor protein myosin-2 (responsible for actin-based motility) 32 (Fig. 5h,i,j, respectively).…”
Section: Ephrin-a5/epha4 Induces Type I Sgn Growth Cone Collapsementioning
confidence: 84%
“…S3o-r). In addition, we found that growth cone collapse coincides with phosphorylation of three potential downstream signalling proteins of EphA4: the guanine nucleotide exchange factor ephexin-1 30 , the actin-depolymerizing and -severing factor cofilin-1 31 and the ATP-dependent motor protein myosin-2 (responsible for actin-based motility) 32 (Fig. 5h,i,j, respectively).…”
Section: Ephrin-a5/epha4 Induces Type I Sgn Growth Cone Collapsementioning
confidence: 84%
“…Organotypic hippocampal slices were prepared as described previously (Zhou et al, 2007). Briefly, 300 m hippocampal slices were prepared from postnatal day 6 (P6) pups and transferred onto semiporous tissue culture inserts (0.4 m pore size; Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…For expressing ChR2 in hippocampal slices, Semliki Forest virus (SFV) constructs were created as described previously (Ehrengruber et al, 1999;Haber et al, 2006;Zhou et al, 2007). The vector pCAGGS-ChR2-Venus was obtained from Addgene (Petreanu et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Farnesylated mCherry (mCherry-f) was created by cloning the farnesylation sequence of Ha-Ras onto the C terminus of mCherry (from R. Tsien, Howard Hughes Medical Institute, University of California, San Diego, La Jolla, CA). Genes for ChR2-Venus and mCherry-f were each cloned 3Ј to a viral subgenomic promoter in a modified SFV vector (SFV-PD) (Lundstrom et al, 2003;Zhou et al, 2007). The SFV-PD vector containing eGFP-f alone was described previously (Haber et al, 2006).…”
Section: Methodsmentioning
confidence: 99%